Fabrication of Glass/Jute/Epoxy Composite Based Industrial Safety Helmet. (2018) - Kumar Bajpai, Pramendra; Ram, Khushi; Kumar Gahlot, Lokesh; Kumar Jha, Vivek
Abstract: This work focused on the development and characterization of hybrid glass/jute reinforced epoxy composite for industrial safety helmet. The total numbers of fiber layers are fixed and by varying the weight percentage of matrix and different fiber layers. Five different composites were manufactured using hand lay-up technique. One layer of glass and three layers of jute reinforce epoxy hybrid composite achieved maximum flexural strength of 100.78 MPa. Three layer of glass and one layer of jute reinforce epoxy hybrid composite achieved maximum impact strength of 72.24 J/m. The study results shows that 3-Glass 1-Jute fiber reinforced epoxy composite which has maximum impact strength can be used to replace the existing industrial safety helmet material.